Acid and Alkaline Etching of Sandblasted Zirconia Implants: A Histomorphometric Study in Miniature Pigs. (9th April 2013) - Saulacic, Nikola; Erdösi, Robert; Bosshardt, Dieter D.; Gruber, Reinhard; Buser, Daniel
Abstract Background Zirconia (ZrO2) has received interest as a dental material; however, little information is available on the impact of surface modifications on the osseointegration of zirconia implants. Purpose The aim of the present study was to determine the effect of acid or alkaline etching of sandblasted ZrO2 implants on bone apposition in vivo. Methods Cylindrical ZrO2 implants with two circumferential grooves were placed in the maxilla of 12 miniature pigs. Biopsies were harvested after 1, 2, 4, and 8 weeks of healing. Undecalcified toluidine blue‐stained ground sections were produced. The bone‐to‐implant contact, the bone area, and the presence of multinucleated giant cells were determined by histomorphometry. An uncorrected explorative statistical analysis was performed. Results Acid etching but not alkaline etching of sandblasted ZrO2 implants caused more bone‐to‐implant contact than sandblasted ZrO2 implants. The bone area was unaffected by the surface modifications. Acid and alkaline etching both increased the formation of multinucleated giant cells at the implant surface. Conclusions This study provides a scientific basis to further investigate the impact of acid etching of sandblasted ZrO2 implants on osseointegration and the role of multinucleated giant cells in this process.